Calcium Supplements and Cardiovascular Disease: A Review. (July 2015) - Waldman, Talya; Sarbaziha, Raheleh; Merz, C. Noel Bairey; Shufelt, Chrisandra
Dietary or supplemental calcium intake has long been encouraged for optimal bone health. However, more recently, the safety of calcium supplementation has been questioned because of a possible association between supplemental calcium and cardiovascular risk. Whereas calcium may have a beneficial or neutral effect on cardiovascular risk factors such as blood pressure, cholesterol, weight, and diabetes, available evidence does not provide a definitive answer for an association with cardiovascular disease (CVD). To date, no calcium trials have studied cardiovascular disease as a primary end point, and larger trials with longer follow-up are needed. In this review, we present results from observational studies and randomized controlled trials (RCTs) that have evaluated calcium intake (dietary or supplemental) in relation to cardiovascular risk factors and cardiovascular disease as a secondary outcome. Results from RCTs are mixed regarding CVD risk in those using supplemental calcium with or without vitamin D, and more large-scale randomized trials designed specifically with CVD as the primary end point are needed. Evidence suggests that it is reasonable to encourage adequate dietary calcium intake, especially for postmenopausal women who are at greatest risk for osteoporotic fracture.